Eco Friendly Synthesis of Pharmaceuticals` (International Journal of Research in Pharmaceutical Sciences and Technology, 2026)
The pharmaceutical industry is increasingly adopting sustainable approaches to reduce environmental pollution while developing safe and effective medicines. Eco-friendly synthesis of pharmaceuticals is a green chemistry approach that focuses on minimizing hazardous chemicals, reducing waste generation, conserving energy, and using renewable resources during drug manufacturing. This strategy helps protect both human health and the environment without compromising the quality of medicines. Green synthesis employs environmentally friendly solvents such as water, ethanol, ionic liquids, and deep eutectic solvents instead of toxic organic solvents. It also utilizes green catalysts, enzymes, microwave-assisted synthesis, ultrasound, and photochemical methods to improve reaction efficiency and reduce energy consumption. These techniques increase product yield, decrease harmful by-products, and lower production costs. Common pharmaceutical examples include the eco-friendly synthesis of Paracetamol, Ibuprofen, and Aspirin, which demonstrate cleaner production methods with reduced environmental impact. The principles of green chemistry, including waste prevention, atom economy, safer chemicals, renewable feed stocks, energy efficiency, and real-time pollution monitoring, form the foundation of sustainable pharmaceutical manufacturing. Compared with conventional synthesis, green synthesis offers significant advantages such as lower toxicity, improved safety, reduced pollution, enhanced product quality, and better resource utilization. This poster highlights the importance of integrating green chemistry into pharmaceutical research and industrial production to achieve sustainable healthcare. Eco-friendly synthesis not only ensures the development of high-quality medicines but also supports environmental conservation and economic growth. By adopting greener technologies today, the pharmaceutical industry can build a healthier future for patients while preserving the planet for future generations. This approach represents a major step toward safe, innovative, and sustainable drug develop.
Keywords: Eco friendly synthesis; Green chemistry; Environmental production; waste reduction; Renewable sources